2009
DOI: 10.1007/s10551-009-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

Does the Individualist Consume More? The Interplay of Ethics and Beliefs that Governs Consumerism Across Cultures

Abstract: consumer ethic, consumerism, ethical behavior, individual values, individualism, protestant work ethic, work ethic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…More collectivist managers were more ethical than less collectivist managers. Lee et al (2010) found a direct relationship between individualism and consumerism, and an inverse relationship between consumerism and consumer ethics. Husted (2000) noted a significant correlation between individualism and software piracy.…”
Section: Hofstede Model and Consumer Ethicsmentioning
confidence: 92%
“…More collectivist managers were more ethical than less collectivist managers. Lee et al (2010) found a direct relationship between individualism and consumerism, and an inverse relationship between consumerism and consumer ethics. Husted (2000) noted a significant correlation between individualism and software piracy.…”
Section: Hofstede Model and Consumer Ethicsmentioning
confidence: 92%
“…As a result, work ethic is now generally understood to be a set of beliefs and values regarding the value of work, which includes these dimensions (Meriac et al, 2010; 147 Work ethic in the United States Miller et al, 2001). Development in psychology and neuroscience lends further support to a multidimensional conceptualization of work ethic (Lee et al, 2010). Numerous studies investigate the relationship between work ethic and various constructs.…”
Section: Work Ethicmentioning
confidence: 99%
“…A logical starting point for such research would be an investigation of the role and development of consumerism in Canada as compared to other developed democratic societies. This effort could build on already existing cross-cultural research in the area (Lee, Anurag and Ali 2010;Varadarajan and Thirunarayana 1990).…”
Section: Conclusion and Implications For Further Researchmentioning
confidence: 99%